Solution of an Electrodynamic Problem for a Homogeneous Equivalent Segment of a Coaxial Load, Considering Heat Losses in the Conductors - Polina V. Tatarenko; Alexander S. Tatarenko (Mathematics, 2022)
Mathematical aspects of solving an electrodynamic problem in the field of designing coaxial devices in the microwave range are considered. The solution of the electrodynamic problem for a homogeneous equivalent segment of a coaxial load in the single-mode approximation, considering the heat losses in the central and outer conductors, was obtained. A mathematical model of the microwave load, linking the high-frequency and design-technological parameters of the device, was built. To refine the model, we consider second-order effects associated with considering inhomogeneities that occur in places where the cross-section of the coaxial structure changes. The design of the 50-Ω load and the results of its experimental investigation are presented for comparison with theoretical calculations.